2023
DOI: 10.1002/ajhb.23886
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of delayed care during the COVID‐19 pandemic: Emerging research and new lines of inquiry for human biologists and anthropologists

Abstract: Objective Research regarding ongoing epidemic or pandemic events is often proximate, focusing on the immediate need to understand the epidemiology of the outbreak and the populations at highest risk for negative outcomes. There are other characteristics of pandemics that can only be uncovered after time has passed, and some long‐lasting health consequences may not be directly linked to infection with or disease from the pandemic pathogen itself. Methods We discuss the emerging literature on observations delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Timely access to care has become a key performance indicator for healthcare systems. Many studies have reported significant increases in overall waiting times during the COVID‐19 pandemic, and the effects of this disruption have persisted 22–24 . However, the prognostic impact of COVID‐19 on patient outcomes following disrupted outpatient care for those referred by PCPs for cardiology consultation has not been systematically evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Timely access to care has become a key performance indicator for healthcare systems. Many studies have reported significant increases in overall waiting times during the COVID‐19 pandemic, and the effects of this disruption have persisted 22–24 . However, the prognostic impact of COVID‐19 on patient outcomes following disrupted outpatient care for those referred by PCPs for cardiology consultation has not been systematically evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, excess mortality puts substantial pressure on public health systems, as observed both historically and during COVID-19 (e.g. van Doren and Brown, 2023 ), leading to delays in treatment of other illnesses, or reductions in resources available for prevention and cure.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, influenza pandemics have given rise to periods of drastically increased mortality. These sharp increases have had important implications for individuals via increased mortality and health risk, as well as for wider society through restrictions, pressure on healthcare systems, and economic effects ( Cohn, 2007 ; Dewitte and Wissler, 2022 ; Maffly-Kipp et al, 2021 ; Neelsen and Stratmann, 2012 ; Ogasawara, 2017 ; Patterson and Pyle, 1991 ; Reid, 2005 ; Shaw-Taylor, 2020 ; van Doren and Brown, 2023 ; Zuijderduijn and De Moor, 2013 ). The health and socioeconomic effects of pandemics have been shown to act unequally across the population, leading to concerns that pandemics might amplify pre-existing inequalities, having the worst effects on the most vulnerable groups in society ( Clay et al, 2019 ; Connor et al, 2020 ; Dewitte and Wissler, 2022 ; Grantz et al, 2016 ; Mamelund, 2006 , 2018 ; Marmot and Allen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%